1986
DOI: 10.1007/bf00269825
|View full text |Cite
|
Sign up to set email alerts
|

Stability of tissue culture medium pH as a function of autoclaving, time, and cultured plant material

Abstract: Autoclaving is a standard procedure for sterilizing nutrient media for plant tissue cultures. Most tissue cultures are grown at pH 5.2 to 5.8 with pH adjustments being made prior to autoclaving. This paper reports that there are significant differences between initial pH levels and pH levels following autoclaving, particularly in the pH range of 5.7 to 8.5. This effect is noted with and without agar. In addition, we report that with time the pH of the medium drifts into the acid range. When Cucumis callus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
7

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 6 publications
7
38
1
7
Order By: Relevance
“…We compared pH changes over time of media stored in two different environments (at 25C in the light and at 4C in darkness). Similar to Skirvin et al (1986), we found that both liquid and agar-solidified culture media stored in the light acidified over time. Storage in darkness at 4C was shown to decrease medium acidification compared to media stored under a standard plant culture environment (at 25C in the light), irrespective of gelling agent addition, type of activated charcoal, or length of storage.…”
Section: Resultssupporting
confidence: 76%
“…We compared pH changes over time of media stored in two different environments (at 25C in the light and at 4C in darkness). Similar to Skirvin et al (1986), we found that both liquid and agar-solidified culture media stored in the light acidified over time. Storage in darkness at 4C was shown to decrease medium acidification compared to media stored under a standard plant culture environment (at 25C in the light), irrespective of gelling agent addition, type of activated charcoal, or length of storage.…”
Section: Resultssupporting
confidence: 76%
“…Various studies have shown that the pH of tissue culture media is poorlycontrolled and shifts both during autoclaving and during culture (e.g. Skirvin et al 1986;Vacin and Went 1949). We obtained similar results (Fig.…”
Section: Stability Of Ph and The Morphogenetic Effect Of Messupporting
confidence: 85%
“…Sự thay đổi pH của môi trường lỏng và môi trường rắn là khác nhau. Trong nghiên cứu của Skirvin et al (1986) [7], môi trường MS rắn và MS lỏng có pH ở 5,7 thì sau khi hấp 1 tuần, pH có giá trị lần lượt là 4,6 và 4,4. Sau 6 tuần, pH giảm xuống là 4,4 đối với môi trường rắn và 4,1 đối với môi trường lỏng.…”
Section: ảNh Hưởng Của Ph Lên Khả Năng Sinh Trưởng Và Phát Triển Của unclassified
“…Ảnh hưởng của pH lên mật độ tế bào (N), khối lượng tươi (FW) và khối lượng khô (DW) của sinh khối tế bào trong môi trường MS lỏng lắc sau 21 ngày nuôi cấy Kết quả thu được sau 21 ngày nuôi cấy cho thấy, khi tăng pH môi trường từ 4,9 đến 6,1, mật độ tế bào, khối lượng tươi và khối lượng khô sinh khối tế bào thu được tăng dần (hình 2). Sự thay đổi pH cũng có khả năng gây ra sự xâm nhập tự do của ion H + vào thành tế bào, tạo ra pH tối ưu cho hoạt động của enzyme nới lỏng thành tế bào [7]. Ion H + trong môi trường sẽ xâm nhập vào thành tế bào, hoạt hóa enzyme phân hủy các polysacarit liên kết giữa các sợi cellulose làm cho chúng lỏng lẻo và tạo điều kiện cho thành tế bào giãn dưới tác dụng của áp suất thẩm thấu của không bào trung tâm, kích thích sự sinh trưởng của tế bào.…”
Section: ảNh Hưởng Của Ph Lên Khả Năng Sinh Trưởng Và Phát Triển Của unclassified